Flood risk of Metro Manila barangays a GIS based risk assessment using multi-criteria techniques - Pornasdoro, Karlo P. (Journal in Urban and Regional Planning, 2014)
Access online through this link: https://journals.upd.edu.ph/index.php/SURP/article/view/4207/3817